ผลของการจัดกิจกรรมการเรียนรู้คณิตศาสตร์โดยใช้เทคนิคพรู้ฟแมปปิงในการเขียนพิสูจน์ทางเรขาคณิตที่มีต่อความสามารถในการให้เหตุผลทางเรขาคณิตของนักเรียนชั้นมัธยมศึกษาปีที่ 2 - กมล นาคสุทธิ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purposes of this research were: 1) to compare geometric reasoning abilities of students between, before and after learning by organizing mathematics learning activities using proof mapping technique to write geometric proofs, 2) to compare geometric reasoning abilities of students between groups being organized mathematics learning activities using proof mapping technique to write geometric proofs and conventional approach, and 3) to study the geometric reasoning ability of students learning by organizing mathematics learning activities using proof mapping technique to write geometric proofs. The population of this research were eighth grade students in Nakhonpathom Education service area office 9 under the office of The Basic Education Commission, Ministry of Education. The subjects were 46 eighth grade students in academic year 2016 at Watraikhingwittaya School. They were divided into two groups, one experimental group with 23 students and the other control group with 23 students. The students in experimental group were organized mathematics learning activities using proof mapping technique to write geometric proofs and those in control group were organized mathematics learning activities using conventional approach. The data collecting instruments were geometric reasoning ability tests. The experimental instruments were lesson plans being organized mathematics learning activities using proof mapping technique to write geometric proofs and the conventional lesson plans. The data were analyzed by means of arithmetic mean, standard deviation and t-test. The results of the study revealed that: 1) the geometric reasoning ability of students after learning by organizing mathematics learning activities using proof mapping technique to write geometric proofs was higher than that before the experiment at .05 level of significance, 2) the geometric reasoning ability of students being organized mathematics learning activities using proof mapping technique to write geometric proofs was higher than that of students being organized mathematics learning activities using conventional approach at .05 level of significance, and 3) the geometric reasoning ability of students learning by organizing mathematics learning activities using proof mapping technique to write geometric proofs was developed in positive direction.